2016
DOI: 10.1038/bmt.2016.306
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia as a possible risk factor for mold infections—the potential preventative role of intensified glucose control in allogeneic hematopoietic stem cell transplantation

Abstract: Diabetes mellitus (DM) is well-known as a disorder that increases the risk of infectious diseases. Various reports have shown that innate immunity is impaired in patients with DM, which is considered to be a major cause of increased risk of infectious diseases. However, there is a paucity of data about the actual risk of mold infections in patients with DM. Several treatment procedures, such as solid organ transplantation and hematopoietic stem cell transplantation (HSCT), are intrinsically associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…17,18 Multiple case series have identified diabetes mellitus as a risk factor for invasive mold infections, but prospective data for improving glucose control in this population are limited. 19 In conclusion, mucormycosis should be considered in patients…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Multiple case series have identified diabetes mellitus as a risk factor for invasive mold infections, but prospective data for improving glucose control in this population are limited. 19 In conclusion, mucormycosis should be considered in patients…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the importance of hyperglycemia should not be underestimated and can be particularly challenging with high‐dose glucocorticoids and calcineurin inhibitors . Multiple case series have identified diabetes mellitus as a risk factor for invasive mold infections, but prospective data for improving glucose control in this population are limited …”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying pathophysiology of the association between hyperglycemia and adverse outcomes is more clearly hypothesized to be related to known immunologic effects such as increased inflammation and impaired leukocyte function, the possible pathophysiologic relationship between glycemic variability and outcomes is less well described 1,15,20‐23 . However, several studies have demonstrated associations between wide glucose fluctuations and both oxidative stress and endothelial cell apoptosis, which may lead to microvascular damage, inflammatory milieu, and disruption of normal immune function 24‐26 .…”
Section: Discussionmentioning
confidence: 99%
“…DM as a complication of major thalassemia is usually manifested after the first decade of life [82,83]. Hyperglycemia in hematological patients may also be the result of infections or certain medications [84][85][86]. For instance, corticosteroids are frequently used for the treatment of both malignant and benign (e.g., immune thrombocytopenia and autoimmune hemolytic anemia) disorders.…”
Section: Hyponatremia Due To Disorders Of Endocrine System and Metabomentioning
confidence: 99%